2020
DOI: 10.1097/ta.0000000000003011
|View full text |Cite
|
Sign up to set email alerts
|

Early versus delayed complex abdominal wall reconstruction with biologic mesh following damage-control surgery

Abstract: BACKGROUND Damage-control surgery for trauma and intra-abdominal catastrophe is associated with a high rate of morbidities and postoperative complications. This study aimed to compare the outcomes of patients undergoing early complex abdominal wall reconstruction (e-CAWR) in acute settings versus those undergoing delayed complex abdominal wall reconstruction (d-CAWR). METHOD This study was a pooled analysis derived from the retrospective and prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This research points to the fact that a short time to surgery is critical for patient survivability, and the present study shows that indeed patients with gastric ulcer perforations all had the shortest time to surgery values for both age groups. A recent retrospective cohort study evaluated patients with complex abdominal wall reconstruction surgery and found that a shorter time to surgery led to a shorter HLOS, which can be predictive of decreased mortality as discussed below [ 34 ]. Additionally, our results showed that the surviving adult group had significantly shorter time to surgery values compared to the deceased group.…”
Section: Discussionmentioning
confidence: 99%
“…This research points to the fact that a short time to surgery is critical for patient survivability, and the present study shows that indeed patients with gastric ulcer perforations all had the shortest time to surgery values for both age groups. A recent retrospective cohort study evaluated patients with complex abdominal wall reconstruction surgery and found that a shorter time to surgery led to a shorter HLOS, which can be predictive of decreased mortality as discussed below [ 34 ]. Additionally, our results showed that the surviving adult group had significantly shorter time to surgery values compared to the deceased group.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this is associated with several wound-related complications and fails to address hernias that are non-midline, subxiphoid, suprapubic, and parastomal as well as those associated with loss of domain 110 . For these reasons, some surgeons have transitioned to using posterior components separation with transverse abdominal release and mesh reinforcement, particularly for the hernias mentioned above 124–126 . In situations where abdominal wall reconstruction is not possible with a mesh and/or component separation, more advanced reconstructive techniques, such as a tensor fascia lata flap can be used 127 , 128 .…”
Section: Abdominal Wall Reconstruction After Open Abdomenmentioning
confidence: 99%
“…Severe injury and oncologic abdomen resection may cause significant abdominal defects 1 . Although primary closure or short-interval defect repair is highly recommended, 2 a complex and massive abdominal wall reconstruction could be challenging in these situations. Stable and adequate coverage is required.…”
mentioning
confidence: 99%